Tren Jilbab Syari dan Polemik Cadar Mencermati Geliat Keislaman Kontemporer di Indonesia - Fathonah Fathonah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
Jilbab, either as a fashion or term, was new known in Indonesia in the 1980s. Although when it got opposition from the ruler, but the unstoppable flow of jilbab flooded the campuses and urban community. thus the new term appears 'shar'i jilbab' and later there is growing fashion dress called cadar. Both the shar'i jilbab or cadar, have full of meaning, importance and full of power, indicating a kind of turmoil of the rise of contemporary Islam from young people in Indonesia. This paper attempts to examine the trend of jilbab and its development to the controversial of the cadar, including what the symptoms are caused in the phenomenon. This paper also provides arguments about the dogmatic religious concepts of the veil system as a form of dress instruction in Islam or only Arab tradition.